Front-end electronics for CMS iRPC detectors. (4th May 2021) - Shchablo, K.; Samalan, A.; Tytgat, M.; Zaganidis, N.; Alves, G.A.; Marujo, F.; Torres Da Silva De Araujo, F.; Da Costa, E.M.; De Jesus Damiao, D.; Nogima, H.; Santoro, A.; Fonseca De Souza, S.; et al.
Abstract: A new generation of resistive plate chambers, capable of withstanding high particle fluxes (up to 2000 Hz · cm -2 ) and instrumented with precise timing readout electronics is proposed to equip two of the four high pseudorapidity stations of the CMS muon system. Double-gap RPC detectors, with each gap made of two 1.4 mm High Pressure Laminate electrodes and separated by a gas gap of the same thickness, are proposed. The new layout reduces the amount of the avalanche charge produced by the passage of a charged particle through the detector. This improves the RPC rate capability by reducing the needed time to collect this charge. To keep the RPC efficiency high, a sensitive, low-noise and high time resolution front-end electronics is needed to cope with the lower charge signal of the new RPC. An ASIC called PETIROC that has all these characteristics has been selected to read out the strips of new chambers. Thin (0.6 mm) printed circuit board, 160 cm long, equipped with pickup strips of 0.75 cm average pitch, will be inserted between the two new RPC's gaps. The strips will be read out from both ends, and the arrival time difference of the two ends will be used to determine the hit position along the strip. Results from the improved RPC equipped with the new readout system and exposed to cosmic muons in the high irradiation environment at CERN GIF++ facility are presented in this work.